Novel Therapies in Headache Disorders - Nichols, Emma Hitt (MD Conference Express, 2014)
Multiple novel therapies have been developed to prevent and treat headaches, many of which target specific points in the pathophysiology of the disorder. This article discusses updates in the understanding of the pathophysiology of headaches, new and emerging treatments for migraine headache, trigeminal autonomic cephalalgias, and the treatment of migraine headaches in children.